Public Service Media in the Age of Digital Networks - Tremblay, Gaëtan (Canadian Journal of Communication, 2016)
For more than fifty years, the public service has been a nexus of media organization, development, and regulation in Canada and several countries in the world. Is public service media still relevant in the age of the internet and digital networks? Before directly addressing this question, this article broadly examines the path that has been hewn by public service media, from its origins—when it played a guiding and influential role in the media landscape—through to today—when its dominance is in question. It links together a set of factors that have triggered a process of redefining public service media, one that may allow it to play the new social and cultural role that is expected of it in contemporary societies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjIwMTZ2NDFuMWEzMDYy